Psikologi Perkembangan Prantal, Usia Dini, Dan Anak: Hakikat Perkembangan Dan Pertumbuhan - Intan S; Media Rahmah; Linda Yarni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Abstract. Development is a pattern of changes experienced by an individual from the time they are still in the womb until a certain period of life. Development generally involves growth (progress) but at certain times it will involve aging. This development is the result of the maturity process and learning experiences of each individual. Development is closely related to tempo and rhythm, it is integral to it. Individuals who experience development can be marked by certain characteristics, but it is not uncommon for individuals to be less aware of the changes that have occurred to them. This research uses a critical review method, which involves careful examination and evaluation of various sources of information, such as scientific journals, articles and other media. The main aim of this approach is to improve the reader’s understanding and interpretation skills in the context of prenatal, early childhood and child development psychology while offering a critical assessment of the material reviewed. In addition, a critical review requires identifying important topics in the literature, analyzing the methodology used, and evaluating the strengths and limitations of the sources studied. In development, there is a pattern of changes experienced by individuals from the time they are still in the womb up to a certain period of life. In a child’s life there are two processes that have the potential to be continuous, namely growth and development. In this case, both processes have stages, including moral and spiritual stages.